Magnetic Properties and Giant Magnetocaloric Effect In Mn-based Heusler Compounds - Dan, Nguyen Huy; An, Nguyen Manh (Communications in Physics, 2013)
Magnetic properties and giant magnetocaloric effect (GMCE) of Mn-based Heusler compounds such as Co-Mn-Si, Ni-Mn-Sn, Ni-Mn-Sb have been investigated. The results show that the structure strongly influences on magnetic properties and GMCE of these alloys. The coexistence of ferromagnetic (FM) and antiferromagnetic (AFM) orders is observed. The magnetic phase transitions can be controlled by changing composition and annealing condition of the alloys. GMCEs with large magnitude and wide working temperature range have been obtained on these alloys showing their application potential for magnetic refrigeration technology.